Neuropathy Associated with Systemic Amyloidosis - Kaku, Michelle; Berk, John L. (Seminars in Neurology, 2019)
Peripheral neuropathy occurs in the setting of both hereditary and acquired amyloidosis. The most common form of hereditary amyloidosis is caused by 1 of 140 mutations in the transthyretin (TTR) gene, which can lead to neuropathic hereditary transthyretin amyloidosis (hATTR; previously referred to as transthyretin familial amyloid polyneuropathy), whereas acquired immunoglobulin light chain (AL) amyloidosis is the most common acquired form. Patients typically present with a sensorimotor polyneuropathy, focal neuropathy such as carpal tunnel syndrome, or autonomic neuropathy. When neuropathy is the sole or dominant presenting symptom, the diagnosis is commonly delayed. With the advent of new drug therapies for AL amyloidosis and hATTR amyloidosis, including proteasome inhibitors, TTR silencers, and TTR protein stabilizers, the neurologist is uniquely positioned to diagnose neurologic manifestations of systemic amyloidosis, leading to earlier disease identification and treatment. This article reviews the epidemiology, clinical presentations, pathophysiology, diagnostic workup, and treatment of neuropathy in the setting of amyloidosis.
Keywords: hereditary neuropathy; transthyretin; AL amyloidosis; primary amyloidosis